نظم اجتماعی میں سیرت طیبہ کی تزکیاتی اور کرداری جہات "حجت اللہ البالغہ" کا خصوصی مطالعہ: Purificational and Ethical Aspects of the Prophetic Sīrah in Social Organization: A Focused Study of Hujjat Allāh al-Bālighah - شاہ جنید احمد ہاشمی (Seerat Studies, 2025)
This research examines the spiritual-purification (tazkiyah) and character-building dimensions of the Prophetic biography (Sīrah), which constitute one of the fundamental pillars in the formation of the Islamic social system. The Messenger of Allah ﷺ did not merely present a structured system of worship and law; rather, he established a strong and harmonious society built upon purification of the soul, moral refinement, and the nurturing of a righteous individual—one who creates a positive impact within his surroundings. This study situates the subject within the comprehensive reformist vision of Shah Waliullah al-Muhaddith al-Dehlawi (1703–1762), one of the foremost revivalists of the Indian subcontinent. He is among the scholars who approached the Sīrah with a maqāṣid-based understanding, presenting a coherent framework in which individual purification becomes the foundation for community-building. His intellectual vision clarifies a holistic model of social reform rooted in the Prophetic example.